The perception of the students of the Career of Medicine at University of Buenos Aires on the treatment of abortion in a medical education - Mines-Cuenya, Ana (Población y Salud en Mesoamérica, 2015)
The aim of this article is to investigate how the approach to abortion and attention in the Career of Medicine of the UBA. To do this, it will emphasize three dimensions. The first is the analysis of emerging Career in light of the laws and regulations that promote sexual rights as a fundamental part of Human Rights (HR). The second analysis is to emerging regarding such discontinuities and ruptures thereby be defined as Hegemonic Medical Model (MMH). Finally, he will inquire into policies, representations and practices regarding misoprostol. This research is qualitative. The corpus analyzed consists of semi-structured interviews to 24 students mentioned Career and national, Latin American and international medical organizations regulations. As preliminary results stand, first, the low permeability in the Career of the regulations, knowledge and pharmacological updates expressed in documents issued by national medical, Latin American and international agencies the past 10 years. Secondly, it highlights the predominance of silence or void in the curriculum in relation to abortion. This silence is not harmless, but has specific effects: not ensure compliance with the human rights framework in force in Argentina. Finally, ignorance about misoprostol and its broad utility in obstetrics and gynecology field reinforces the asymmetry in the medical / a-patient relationship and a sense of medicalized abortion, therefore, strengthens the MMH.